Writing in French in secondary schools in England and Germany: are the British really 'bad language learners'?. Issue 3 (3rd July 2017) - Gruber, Alice; Tonkyn, Alan
Abstract : It is widely assumed that the British are poorer modern foreign language (MFL) learners than their fellow Europeans. Motivation has often been seen as the main cause of this perceived disparity in language learning success. However, there have also been suggestions that curricular and pedagogical factors may play a part. This article reports a research project investigating how German and English 14- to 16-year-old learners of French as a first foreign language compare to one another in their vocabulary knowledge and in the lexical diversity, accuracy and syntactic complexity of their writing. Students from comparable schools in Germany and England were set two writing tasks which were marked by three French native speakers using standardised criteria aligned to the Common European Framework of Reference (CEF). Receptive vocabulary size and lexical diversity were established by the X_lex test and a verb types measure respectively. Syntactic complexity and formal accuracy were respectively assessed using the mean length of T-units (MLTU) and words/error metrics. Students' and teachers' questionnaires and semi-structured interviews were used to provide information and participants' views on classroom practices, while typical textbooks and feedback samples were analysed to establish differences in materials-related input and feedback in the two countries. The German groups were found to be superior in vocabulary size, and in the accuracy, lexical diversity and overall quality – but not the syntactic complexity – of their writing. The differences in performance outcomes are analysed and discussed with regard to variables related to the educational contexts (e.g. curriculum design and methodology).